Fabrication of p-type porous silicon for improved Raman efficiency in low concentration SERS detection / Jamilah Mat Tapah - Mat Tapah, Jamilah (2025)
Surface-enhanced Raman scattering (SERS) is a powerful tool for detecting low concentrations of analytes, but the high cost and instability of traditional metallic substrates limit its applications. To overcome these challenges, this study focuses on the fabrication of p-type porous silicon (PSi) as a cost-effective and reliable SERS substrate. A photo-electrochemical etching process was employed to create PSi, with etching times varied to optimize pore structures. Silver nanoparticles (AgNp’s) of 5nm and 75nm sizes were deposited on the PSi surface to enhance Raman signal amplification through plasmonic effects. Structural characterization using Field Emission Scanning Electron Microscopy (FESEM) revealed that a 25 minutes etching time produced uniform and deep pores, maximizing surface area and hotspot distribution. Electrical properties were assessed using current-voltage (I-V) measurements, confirming improved conductivity with AgNp integration. Raman efficiency was evaluated using Rhodamine 6G (R6G) as a model analyte, where the 75nm AgNp’s provided stronger signal enhancement compared to the 5nm particles. The optimized substrates demonstrated high sensitivity and reliability in detecting low concentrations of R6G. By combining precise fabrication methods with thorough structural, electrical, and optical characterization, this study presents a robust, affordable approach to advancing SERS technology. The findings highlight the potential of p-type PSi substrates for a wide range of applications, including noninvasive diagnostics, environmental monitoring, and chemical sensing, offering significant improvements in sensitivity, stability, and reproducibility over traditional methods.